Przeobrażenia celów i wartości przedsiębiorstwa w kontekście zmian otoczenia zewnętrznego - Głuszek, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The growing trends that have been observed in our social environment provided a reflection in company's management system in area of defined objections and lasting values, which next have an impact on the used methods, practices, structures, processes and regulations. The article analyses the influence of the most meaningful social and cultural trends on the changes of objectives and values hold in companies. It also points at the further consequences for the other factors of the management system. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 27-37